Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Anti-thrombocytopenic activity of Carica papaya L. cv. Red Lady leaf aqueous fraction in thrombocytopenic rat model: An investigation on blood plasma proteomic analysis - Arya J; Krishnakumar K; Evelyn Maria; Alex George; Mathew John (South African Journal of Botany, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Efficient synthetic natural gas production from direct air capture using titania-based dual function materials - Mathew J. Rasmussen; Sawyer Halingstad; Nathan C. Ellebracht; Melinda L. Jue; Alex Hill; Matthew M. Yung; Simon H. Pang (Chemical Engineering Journal, 2025)

Overview of the WIO-Benth Project – benthic habitats and megafauna from soft sediments in the Western Indian Ocean - Sean Fennessy; Bernadine Everett; Fiona MacKay; Silvia Abdula; Jean Jacaques Be; Andrew Green; Chris Jenkins; Esther Fondo; Cang Hui; Amon Kimeli; Mary Kishe; Alex Mafuru; et al. (Western Indian Ocean Journal of Marine Science, 2025)
The Western Indian Ocean (WIO) hosts substantial marine biodiversity, which is better known from inshore and coastal hab- itats. The diversity from soft sediments of the shelf and slope is much less known regionally, which was the premise for the WIO-Benth Project. Existing seabed information and bottom trawl catch data were compiled for five countries (Kenya, Tanza- nia, Mozambique, South Africa, and Madagascar), to characterize seabed habitats and benthic (demersal trawl) communities of the continental shelf and upper slope in the western part of the WIO. Soft sediment (sand, mud) habitats were spatially dominant (54 %) relative to rock/mixed habitats; associated trawled fauna from these habitats were dominated by Chordata (fishes) and Arthropoda (mainly crustaceans). This overview of the special issue on the WIO-Benth Project provides a summary of the general results, greater details on which are provided in the issue’s constituent papers. In the process of compiling infor- mation and data from the region, the WIO-Benth Project has provided new knowledge to assist with marine spatial planning and decision-making in the WIO.

Overview of the WIO-Benth Project – benthic habitats and megafauna from soft sediments in the Western Indian Ocean - Sean Fennessy; Bernadine Everett; Fiona MacKay; Silvia Abdula; Jean Jacaques Be; Andrew Green; Chris Jenkins; Esther Fondo; Cang Hui; Amon Kimeli; Mary Kishe; Alex Mafuru; et al. (Western Indian Ocean Journal of Marine Science, 2025)
The Western Indian Ocean (WIO) hosts substantial marine biodiversity, which is better known from inshore and coastal hab- itats. The diversity from soft sediments of the shelf and slope is much less known regionally, which was the premise for the WIO-Benth Project. Existing seabed information and bottom trawl catch data were compiled for five countries (Kenya, Tanza- nia, Mozambique, South Africa, and Madagascar), to characterize seabed habitats and benthic (demersal trawl) communities of the continental shelf and upper slope in the western part of the WIO. Soft sediment (sand, mud) habitats were spatially dominant (54 %) relative to rock/mixed habitats; associated trawled fauna from these habitats were dominated by Chordata (fishes) and Arthropoda (mainly crustaceans). This overview of the special issue on the WIO-Benth Project provides a summary of the general results, greater details on which are provided in the issue’s constituent papers. In the process of compiling infor- mation and data from the region, the WIO-Benth Project has provided new knowledge to assist with marine spatial planning and decision-making in the WIO.

Coexistence beyond disciplinary silos: Five dimensions of analysis for more convivial human-predator interactions - Judith E. Krauss; Valentina Fiasco; Silvio Marchini; Alex McInturff; Laila T. Sandroni; Peter S. Alagona; Dan Brockington; Bram Büscher; Rosaleen Duffy; Katia Maria P M de Barros Ferraz; Rob Fletcher; Wilhelm Andrew Kiwango; et al. (Biological Conservation, 2025)

Interference for MIPS1 mRNA results in biofortified lablab (Lablab purpureus L.) lines having reduced phytic acid levels - Feba Jacob; Deepu Mathew; K.B. Soni; Swapna Alex; Seeja Thomachan Panjikkaran (Biocatalysis and Agricultural Biotechnology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Exploring machine learning models to predict atmospheric water harvesting with an ion deposition membrane - Giulio Barletta; Shashwata Moitra; Sybil Derrible; Alex Mathew; Anoop Muraleedharan Nair; Constantine M. Megaridis (Journal of Water Process Engineering, 2025)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Bluish-white Light-emitting 2D Sheets of Lead-free Perovskite Cesium Titanium Bromide (CsTiBr3) by a Two-stage Deposition Technique - K A Benazeera Beegum; Saranya Sasi; Christeena Thomas; Alex Mathew; Reshmi Raman (Journal of Fluorescence, 2024)

Novel community data in ecology-properties and prospects - Florian Hartig; Nerea Abrego; Alex Bush; Jonathan M. Chase; Gurutzeta Guillera-Arroita; Mathew A. Leibold; Otso Ovaskainen; Loïc Pellissier; Maximilian Pichler; Giovanni Poggiato; Laura Pollock; Sara Si-Moussi; et al. (Trends in Ecology & Evolution, 2024)

The effects of plastic additives on swimming activity and startle response in marine amphipod Echinogammarus marinus - Bidemi Green-Ojo; Hung Tan; Marina Tenório Botelho; Henry Obanya; Lena Grinsted; Mathew O. Parker; Alex T. Ford (Science of The Total Environment, 2024)

Isolation of intake mediated effects demonstrate that the phenomic benefits of dietary omega-3 are nominal to Atlantic salmon when reared in a challenging (hypoxic) environment - Brett D. Glencross; Alex Berry; Ben Clokie; Ernst Hevroy; David Huyben; Laura Martinez-Rubio; Chessor A. Mathew; Pedro Munoz; Simon MacKenzie; Rod W. Wilson (Aquaculture, 2024)

Evaluation of precopulatory pairing behaviour and male fertility in a marine amphipod exposed to plastic additives - Bidemi Green-Ojo; Marina Tenório Botelho; Gisela de Aragão Umbuzeiro; Vicente Gomes; Mathew O. Parker; Lena Grinsted; Alex T. Ford (Environmental Pollution, 2024)

The production-protection nexus: How political-economic processes influence prospects for transformative change in human-wildlife interactions - Robert Fletcher; Kate Massarella; Katia M.P.M.B. Ferraz; Wilhelm A. Kiwango; Sanna Komi; Mathew B. Mabele; Silvio Marchini; Anja Nygren; Laila T. Sandroni; Peter S. Alagona; Alex McInturff (Global Environmental Change, 2023)

The relationship between single muscle fibre and voluntary rate of force development in young and old males - Benjamin E. Dalton; Nicole Mazara; Mathew I. B. Debenham; Derek P. Zwambag; Alex M. Noonan; Erin Weersink; Stephen H. M. Brown; Geoffrey A. Power (European Journal of Applied Physiology, 2023)

Circulating testosterone and dehydroepiandrosterone are associated with individual motor unit features in untrained and highly active older men - Yuxiao Guo; Jessica Piasecki; Agnieszka Swiecicka; Alex Ireland; Bethan E. Phillips; Philip J. Atherton; Daniel Stashuk; Martin K. Rutter; Jamie S. McPhee; Mathew Piasecki (GeroScience, 2022)
Long-term exercise training has been considered as an effective strategy to counteract age-related hormonal declines and minimise muscle atrophy. However, human data relating circulating hormone levels with motor nerve function are scant. The aims of the study were to explore associations between circulating sex hormone levels and motor unit (MU) characteristics in older men, including masters athletes competing in endurance and power events. Forty-three older men (mean ± SD age: 69.9 ± 4.6 years) were studied based on competitive status. The serum concentrations of dehydroepiandrosterone (DHEA), total testosterone (T) and estradiol were quantified using liquid chromatography mass spectrometry. Intramuscular electromyographic signals were recorded from vastus lateralis (VL) during 25% of maximum voluntary isometric contractions and processed to extract MU firing rate (FR), and motor unit potential (MUP) features. After adjusting for athletic status, MU FR was positively associated with DHEA levels ( p = 0.019). Higher testosterone and estradiol were associated with lower MUP complexity; these relationships remained significant after adjusting for athletic status ( p = 0.006 and p = 0.019, respectively). Circulating DHEA was positively associated with MU firing rate in these older men. Higher testosterone levels were associated with reduced MUP complexity, indicating reduced electrophysiological temporal dispersion, which is related to decreased differences in conduction times along axonal branches and/or MU fibres. Although evident in males only, this work highlights the potential of hormone administration as a therapeutic interventional strategy specifically targeting human motor units in older age.

Lifelong exercise is associated with more homogeneous motor unit potential features across deep and superficial areas of vastus lateralis - Eleanor J. Jones; Jessica Piasecki; Alex Ireland; Daniel W. Stashuk; Philip J. Atherton; Bethan E. Phillips; Jamie S. McPhee; Mathew Piasecki (GeroScience, 2021)
Motor unit (MU) expansion enables rescue of denervated muscle fibres helping to ameliorate age-related muscle atrophy, with evidence to suggest master athletes are more successful at this remodelling. Electrophysiological data has suggested MUs located superficially are larger than those located deeper within young muscle. However, the effects of ageing and exercise on MU heterogeneity across deep and superficial aspects of vastus lateralis (VL) remain unclear. Intramuscular electromyography was used to record individual MU potentials (MUPs) and near fibre MUPs (NFMs) from deep and superficial regions of the VL during 25% maximum voluntary contractions, in 83 males (15 young (Y), 17 young athletes (YA), 22 old (O) and 29 master athletes (MA)). MUP size and complexity were assessed using area and number of turns, respectively. Multilevel mixed effects linear regression models were performed to investigate the effects of depth in each group. MUP area was greater in deep compared with superficial MUs in Y ( p <0.001) and O ( p =0.012) but not in YA ( p =0.071) or MA ( p =0.653). MUP amplitude and NF MUP area were greater, and MUPs were more complex in deep MUPs from Y, YA and O (all p <0.05) but did not differ across depth in MA (all p >0.07). These data suggest MU characteristics differ according to depth within the VL which may be influenced by both ageing and exercise. A more homogenous distribution of MUP size and complexity across muscle depths in older athletes may be a result of a greater degree of age-related MU adaptations.

Omega-3 Fatty Acid Protects Against Arsenic Trioxide-Induced Cardiotoxicity In Vitro and In Vivo - Mathews V. Varghese; M. Abhilash; M. V. Sauganth Paul; Manju Alex; R. Harikumaran Nair (Cardiovascular Toxicology, 2017)

Age-dependent motor unit remodelling in human limb muscles - Mathew Piasecki; Alex Ireland; David A. Jones; Jamie S. McPhee (Biogerontology, 2016)

Effect of ethanol extract of Sphaeranthus indicus on cisplatin-induced nephrotoxicity in rats - Jessy Elizabeth Mathew; Alex Joseph; Keloth Srinivasan; Seekarajapuram Vachala Dinakaran; Anand Mantri; Vinit Movaliya (Natural Product Research, 2012)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)